Effect of exercise on the maternal outcome in pregnancy of spontaneously hypertensive rats - Rocha, Renato; Peraçoli, José Carlos; Volpato, Gustavo Tadeu; Damasceno, Débora Cristina; Campos, Kleber Eduardo De (Sociedade Brasileira para o Desenvolvimento da Pesquisa em Cirurgia, 2014)
PURPOSE:To evaluate the effect of exercise (swimming) on pregnancy in spontaneously hypertensive rats (SHR). METHODS:Thirty three pregnant female SHR were distributed into three groups (n=11 animals/group): SHR Control=non-exercised (sedentary); SHR Ex0 = exercised from day zero to day 20 of pregnancy; and SHR Ex7 = exercised from day 7 to 20 of pregnancy. Body weight and systolic blood pressure were indirectly measured during pregnancy. On gestational day 21, the rats were anaesthetized and uterine content was withdrawn for analysis of maternal reproductive outcome parameters and fetal development. RESULTS:The reduced blood pressure percentage was higher in SHR Ex0 and SHR Ex7 compared to SHR Control group. Weight gain was present in all pregnancy periods, but it was lower in SHR Ex7 than in SHR Control dams. The exercise increased the pre-implantation loss rate. The post-implantation loss rate was lower in SHR Ex0 group. SHR Ex7 group showed a significantly higher percentage of fetuses classified as small for gestational age as compared to others groups. CONCLUSION:The exercise contributed to lowering gestational blood pressure in SHR rats, but had a negative impact on the developing embryo.
Keywords: Exercise; Hypertension; Pregnancy; Rats, Inbred SHR